Studi kasus kanjuruhan: Analisis penyebab, dampak, dan upaya pencegahan tragedi keselamatan publik di Indonesia - Mubarok, Azmi sahlul (Maliki Interdisciplinary Journal, 2025)
The Kanjuruhan tragedy on October 1, 2022, in Malang, East Java, stands as one of the most devastating incidents in Indonesian and world football history. More than 130 people lost their lives and hundreds were injured due to chaos after the match between Arema FC and Persebaya Surabaya. This article analyzes the causal factors, the multidimensional impacts, and prevention strategies to avoid similar incidents in the future. Using risk management theory, public safety, and social responsibility approaches, this study highlights weaknesses in stadium safety systems, procedural errors by security forces, and lack of preparedness by organizers. The findings emphasize the need for comprehensive reforms in Indonesia's sports event management.